ANALYSIS OF EXPENDITURE BUDGET PERFORMANCE IN THE BUDGET REALIZATION REPORT DPRD SECRETARIAT OF SOUTH KALIMANTAN PROVINCE - Hikmahwati; Raudatul Jennah; Rizky Amelia (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The Budget Realization Report presents a budget report, which shows how resources are allocated and used. This research aims to determine the performance of the expenditure budget in the budget realization report. This research was conducted at the DPRD Secretariat of Kalimantan Selatan Province. The type of research used is quantitative descriptive research. The data used is the 2019-2021 budget. The performance of the spending budget is measured using spending variance analysis, spending harmony analysis, efficiency ratios, and spending effectiveness. Then, analyze the problems that occur with the performance of the expenditure budget to produce conclusions from the results of the analysis carried out and provide suggestions. The research results show that the comparison of budget and actual expenditure using expenditure variance analysis in 2019-2021 has good budget performance because actual expenditure does not exceed the budget. If seen from the analysis of the harmony of operating expenditure, 2019 had a good performance, while in 2020 and 2021 the budget performance was not equal, because it exceeded the specified proportion. Meanwhile, the 2019-2021 capital expenditure harmony analysis performed well, because the proportion value was no more than 5-20%. The efficiency ratio for 2019-2021 shows efficiency because the expenditure criteria achieved are less than 100%. Meanwhile, the effectiveness ratio for 2019-2021 shows that it is effective because the criteria achieved are more than 100%.